Biopsychosocial frailty and the risk of incident dementia: The Italian longitudinal study on aging. Issue 8 (2nd July 2019) - Solfrizzi, Vincenzo; Scafato, Emanuele; Lozupone, Madia; Seripa, Davide; Schilardi, Andrea; Custodero, Carlo; Sardone, Rodolfo; Galluzzo, Lucia; Gandin, Claudia; Baldereschi, Marzia; Di Carlo, Antonio; Inzitari, Domenico; et al.
Abstract: Introduction: Frailty is a critical intermediate status of the aging process including physical, cognitive, and psychosocial domains/phenotypes. We operationalized a new biopsychosocial frailty (BF) construct, estimating its impact on the risk of incident dementia and its subtypes. Methods: In 2171 older individuals from the population‐based Italian Longitudinal Study on Aging (ILSA), we identified by latent class procedures the BF construct as the physical frail status plus at least one of the two items of the 30‐item Geriatric Depression Scale impaired (items 3/10). Results: Over a 3.5‐year follow‐up, participants with BF showed an increased risk of overall dementia (hazard ratio [HR]: 2.16, 95% confidence interval [CI]:1.07‐4.37), particularly vascular dementia (VaD) (HR: 3.21, 95% CI: 1.05‐9.75). Similarly, over a 7‐year follow‐up, an increased risk of overall dementia (HR: 1.84, 95% CI: 1.06‐3.20), particularly VaD (HR: 2.53, 95% CI: 1.08‐5.91), was also observed. Discussion: In a large cohort of Italian older individuals without cognitive impairment at baseline, a BF model was a short‐ and long‐term predictor of overall dementia, particularly VaD.